(untitled) (Research, Society and Development, 2021)
This paper describes what the sacrifice is for consumption and proposes a scale to measure the sacrifice for (not) buying products. A multimethod approach was applied to achieve the proposed objectives. Initially, three qualitative studies were carried out (two focus groups and one interview with experts). Then, three quantitative studies were conducted (two online and a survey), and finally, two factorial experiments, 2x2 were developed. The act of sacrifice was understood as an exchange process in which some kind of benefit is sought, a fact that also consolidates the definition of sacrifice presented as the willingness to give up something that has value (monetary or not) in order to obtain some benefit (emotional and/or material) of greater importance. Furthermore, the existence of positive and negative elements in the sacrifice for (not) buying products, described as valence and instrumentality, respectively, was identified. It was also found that different levels of valence and instrumentality affect purchase intent. The elements that comprise the sacrifice for (not) buying products were presented, highlighting a definition that can reduce the doubts about what sacrifice is in the context of consumption, as well as how to measure it.